Removal Of Cod And Color From Stabilized Landfill Leachate Using Fenton, Electrochemical And Electro-Fenton Processes - Mohajeri, Soraya (2010)
In recent years, advanced oxidation processes (AOPs) have been used for degradation of biorecalcitrant organics with some success. Nevertheless, application of electro-Fenton was not established well for landfill leachate treatment. Additionally, optimized process conditions and the interaction among process parameters are unknown and it is a large gap in landfill leachate treatment knowledge. This study aimed to compare the efficiency of three AOP techniques viz., Fenton, electrochemical and electro-Fenton separately at different experimental conditions with specific emphasize on electro-Fenton oxidation.